2015
DOI: 10.1111/1346-8138.13084
|View full text |Cite
|
Sign up to set email alerts
|

Case with Brunsting–Perry‐like localized subepidermal blister formations and immunoglobulin G antibodies against unidentified basement membrane zone antigen

Abstract: Brunsting-Perry type bullous pemphigoid is defined by the blister formation limited to the head and neck, and autoantibodies to type VII collagen are detected in several cases. However, the pathomechanisms and autoantigens in this condition remain unknown. We report a 20-year-old female patient with a more than 2-year history of recurrent tense blisters localized on the face with no distinct atrophic scar formation. The patient had neither extensive sun exposure nor a history suggestive of contact dermatitis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Two cases of BPP were reported with a positive ELISA for laminin-332 (laminin-5) [4]. Also, there is a report of direct and indirect immunofluorescence IgG positivity in the basement membrane zone, but no known dermal or epidermal autoantigens were detected in the immunoblot analyzes, suggesting a rare variant of BPP with autoantibodies to an indeterminate antigen from the basal membrane zone [6]. Finally, a case was described with a discrepancy between the blistering level (intra-lamina lucida) and the location of antigen (lamina densa and sub-lamina densa areas); it can be concluded that BPP includes cases showing characteristics of EBA as well as BP [7].…”
Section: Discussionmentioning
confidence: 99%
“…Two cases of BPP were reported with a positive ELISA for laminin-332 (laminin-5) [4]. Also, there is a report of direct and indirect immunofluorescence IgG positivity in the basement membrane zone, but no known dermal or epidermal autoantigens were detected in the immunoblot analyzes, suggesting a rare variant of BPP with autoantibodies to an indeterminate antigen from the basal membrane zone [6]. Finally, a case was described with a discrepancy between the blistering level (intra-lamina lucida) and the location of antigen (lamina densa and sub-lamina densa areas); it can be concluded that BPP includes cases showing characteristics of EBA as well as BP [7].…”
Section: Discussionmentioning
confidence: 99%
“…Only four younger patients with BPMMP, aged 20–33 years old, were described so far, including two males [M] and two females [F] [Sugita (2001) F/33, Minato (2011) M/31, Sato-Shibuya (2016) F/20, Person (1976) M/29]. 6 , 22–24…”
Section: Discussionmentioning
confidence: 99%
“…11 , 26 Differential diagnosis is additionally complicated by the fact that in some patients with BPMMP, antibodies to type VII collagen, localized in the lower lamina densa and sub-lamina densa have been described which are typical for EBA. 3 , 6 , 10 , 21 , 23 , 28 Consequently, some authors have suggested that Brunsting-Perry CP may represent a clinical, localized variant of EBA 3 , 28–32 . In the study by Joly et al the patient had the typical clinical features of Brunsting-Perry MMP, however DIF studies on salt-split peribullous skin showed IgG and C3 deposits located exclusively on the floor and not on the roof of the blister in a pattern usually found in patients with EBA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation